Strategi Guru PAI dalam Meningkatkan Motivasi Belajar Siswa SMPN 1 Wih Pesam, Bener Meriah - Eliana (Tadabbur: Jurnal Peradaban Islam, 2021)
A teacher has a big responsibility in the teaching and learning process. Therefore, the teacher must motivate the students because motivation is one factor that can affect the success or failure of all student activities in learning. This study aims to determine the strategies of Islamic Education teachers in increasing learning motivation, efforts of Islamic Education teachers in increasing student motivation, and to find out the obstacles and solutions as an effort of Islamic Education teachers in increasing student motivation of Junior High School in the sub-district of Wih Pesam, Bener Meriah Regency. This study is through a qualitative approach with data collection techniques through observation, interviews, and documentation studies. The results of the study concluded that the Islamic Education teacher strategy in increasing student learning motivation Junior High School in the sub-district of Wih Pesam, Bener Meriah Regency can be done with several steps, including; explain learning objectives to students, give gifts (rewards), bring up rivals or competencies, give praise, provide penalties and sanctions, generate encouragement to learn, form good learning habits, help students learning difficulties both individually and in groups, using various methods and must be by the learning objectives. Islamic education teachers' efforts in increasing learning motivation can be made through two motivational approaches, both intrinsic and extrinsic motivation. Intrinsic motivation can be done utilizing; giving gifts (reward), giving positive competence, giving advice and guidance, giving punishment or sanctions. While the extrinsic motivation approach can be made using the suitable method, the teacher must be creative, carry out self-reflection for students, give responsibility to students, make changes to the learning atmosphere, learning objectives must be clear, and identify student learning outcomes. While the obstacles faced by Islamic Education teachers are: still lack of reading books, lack of motivation from parents, improper learning methods used, and lack of interest in students in Islamic Education. While the solution is; foster students' interest in Islamic Education lessons, provide advice and guidance, give parents advice, and add activities to Islamic Education.